IMPLEMENTASI PROGRAM KAMPUS MENGAJAR DALAM MENINGKATKAN LITERASI DAN NUMERASI MURID SDN KIP MACCINI KOTA MAKASSAR - Nugrah Alvina; Muhammad Nawir; Wahyuddin (STKIP Subang, 2024)
The Teaching Campus is a learning channel that provides students with the opportunity to study outside campus for one semester to practice their ability to solve complex problems by becoming partners with teachers to innovate in learning, develop strategies and learning models that are creative, innovative and fun. The purpose of this research is to determine the implementation of the Teaching Campus Program in improving the literacy and numeracy of Kip Maccini Elementary School students